Relationships between psychometrically distinct Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS) factors and mental health among U.S. college students. Issue 2 (7th February 2021) - Smith, Erin I.; Yoon, Dong Pil; Bruininks, Patricia; Witvliet, Charlotte V. O.; Cohen, Daniel; Edman, Laird R. O.; Bankard, Joseph; Johnstone, Brick
ABSTRACT: The current study tested the extent to which demographic, personality, spiritual, and religious variables accounted for variance in physical and mental health measures using recently identified psychometrically distinct factors of the Brief Multidimensional Measure of Religiousness/Spirituality. Based on a non-clinical sample of 249 U.S. undergraduate students, hierarchical multiple regressions were significant for mental, but not physical, health, with 33% of the variance explained by demographic and personality measures and an additional 8% of the variance explained by measures of spirituality (i.e., positive and negative) but not religiosity. The results confirm that spiritual variables are unique predictors of mental health beyond demographics and personality, as well as a need to consider both positive and negative spiritual beliefs when predicting mental health.